Premenstrual dysphoric disorder: reviews of studies in Malaysia, measures used, and validation of the daily record of severity of problems - Hasim @ Hashim, Siti Inarah; Abdul Khaiyom, Jamilah Hanum (Penerbit Universiti Sains Malaysia, 2019)
Premenstrual Dysphoric Disorder (PMDD) is the most severe form of Premenstrual Syndrome (PMS). It impacts the lives and productivity of women worldwide. The literature review found eight studies conducted on PMS and menstruation in Malaysia. However, none of these studies focused on PMDD and reported the utilization of psychometrically valid and reliable tools in assessing it. One of the common measures used to assess PMDD is Daily Record of Severity of Problems (DRSP). Items in DRSP are based on the Diagnostic and Statistical Manual of Mental Disorders, Fifth edition. Currently, there are two published studies on the validation of DRSP and its psychometric properties which will be discussed in this paper. The review shows that an ongoing adaptation and validation study of DRSP among Malaysian is being conducted. This will contribute to the body of knowledge regarding PMDD in local settings.